2013
DOI: 10.5333/kgfs.2013.33.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Harvest Stage of Italian Ryegrass 'Kowinearly' According to One and Two Harvests During Spring Season

Abstract: This study was carried out to determine the optimum harvest stage of Italian ryegrass (Lolium multiflorum Lam., IRG) for maximum forage production during the spring season in Suwon, 2010. The variety of IRG was the early maturity type, 'Kowinearly', and six harvest stages (treatments) were first heading (T1), heading (T2), late heading to early bloom (T3), bloom to late bloom (T4), ripeness (T5), and late ripeness stage (T6). The dates of the first heading and heading of 'Kowinearly' were seen on 4 to 5 May, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This is because as cultivation period increases, maturity stages develop and the leaf ratio of the plant decreases and stems harden Lim and Kim;. The chemical compositions of forage crop were reported represent significant differences depending on cutting times (Hwang et al, 2008), maturity stage (Seo et al, 2013), varieties ( Kim et al, 1998), seeding dates (Kim et al, 2009) and manure conditions (Lee, 2012). Feed value was shown to be high in the late seeding group (T4, T5), but as shown in …”
Section: Chemical Compositionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because as cultivation period increases, maturity stages develop and the leaf ratio of the plant decreases and stems harden Lim and Kim;. The chemical compositions of forage crop were reported represent significant differences depending on cutting times (Hwang et al, 2008), maturity stage (Seo et al, 2013), varieties ( Kim et al, 1998), seeding dates (Kim et al, 2009) and manure conditions (Lee, 2012). Feed value was shown to be high in the late seeding group (T4, T5), but as shown in …”
Section: Chemical Compositionsmentioning
confidence: 99%
“…Also Italian rye grass has a higher ratio of leaves to stems which makes it high silage quality. It is a plant that can produce dry hay in spring season (Seo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference between the ADF and TDN content in relation to seeding date. The chemical compositions of forage crops differ significantly, depending on cutting time [23], maturity stage [24], variety [2], seeding date [2], and manure conditions [25]. In the present study, feed value appeared to be high in the late seeding groups (T4 and T5); however, as shown in Table 4, when the seeding date is late, there is a significant decrease in yield.…”
Section: Resultsmentioning
confidence: 63%
“…Light, temperature, water, and mineral nutrition are essential resources regulating forage grass regrowth and yield (Lee et al, 2021;Nambiar, 1977;Seo et al, 2013). Nassiri and Elgersma (2002) found that nitrogen fertilizer has a growth-limiting effect on ryegrass regrowth.…”
Section: Introductionmentioning
confidence: 99%